BIODIVERSITY IMPORTANT FACTORS ASSESSMENT ON LOWLAND TROPICAL FOREST BY ECOLOGICAL QUANTITATIVE PARAMETERS - Farida Herry Susanty (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2016)
Biodiversity assessment, even in natural forest production has become one important view to consider the balanced ecology in order to maintain productivity function. Most recent studies indicated the partial approach to biodiversity valuation then would provide occurmultiple or difference view. This study aims at identifying the biodiversity important factors as assessment tools on lowland tropical forest by ecological quantitative parameters approach. The study was conducted on Labanan forest research station as lowland tropical forest that is located in Berau district East Kalimantan Province. Data collecting from permanent research plots that consist of 3 variations of logged over forest with different logging techniques and primary condition as control with total area of 48 ha, which measurement conducted periodically every two years along 24 years. Arrangement of ecological important variables based on fluctuation values of the quantitateive dimension which included: density (number of stems), basal area, number of species, shannon diversity index, species abundance, richness index andevenness index. To identify important variables of performance characteristics of biodiversity assessment using by factor analysis basedon Bartlett's Test of Sphericity with value of KMO (Kaiser Meyer Olkin) then the principal component dispersion using Biplot analysis. Determination of important variables based on minimum coefficient variance with total proportion cumulative percentage >80% and eigenvalue >1. The tendency towards of important ecological parameters as biodiversity assessment approach of lowland tropical forest stands after logging could be concluded by 2 important factors are evenness index and species abundancy value. Key words: biodiversity, ecological, lowland tropical forest, quantitative parameters